Goosebumps Be Careful What You Wish For .. - Stine, R. L. (Scholastic NEW YORK, 1993)
Samantha Byrd is a klutz. An accident waiting to happen. She's the laughingstock of the girl's basketball team. And that mean, rotten Judith Bellwood is making her life miserable on and off the court. But everything's about to change. Sam's met someone who can grant her three wishes. Too bad Sam wasn't careful what she wished for. Because her wishes are coming true. And they're turning her life into a living nightmare!!!